Learning Model Course Choukai through Shadowing Technique - Zia, Najma Chalida; Karnawati, Rita Agustina (Universitas Muhammadiyah Yogyakarta, 2022)
Shadowing is considered an effective way to improve listening, speaking and reading skills. This paper aims to develop a learning model choukai with shadowing techniques and to determine the effectiveness of using shadowing techniques on listening ability in choukai courses. Therefore, experimental research and data collection techniques using pre and post-tests were applied to the same group, consisting of 28 students. Then, the t-test was used to analyze the data. As a result, there was a significant difference between the pre-test and the post-test result, indicating that the Sig. (2-tailed) of 0.000 0.05, and a difference between the average student results before and after using shadowing techniques after treatmeant. In conclusion, developing of the learning model choukai using shadowing techniques on level IV students of the Japanese language education study program FKIP UHAMKA was feasible to be used by students in learning courses choukai.